Recent Advancements in Poor Graft Function Following Hematopoietic Stem Cell Transplantation - Man, Yan; Lu, Zhixiang; Yao, Xiangmei; Gong, Yuemin; Yang, Tonghua; Wang, Yajie (Frontiers in Immunology, 2022)
Poor graft function (PGF) is a life-threatening complication that occurs after transplantation and has a poor prognosis. With the rapid development of haploidentical hematopoietic stem cell transplantation, the pathogenesis of PGF has become an important issue. Studies of the pathogenesis of PGF have resulted in some success in CD34+-selected stem cell boosting. Mesenchymal stem cells, N-acetyl-l-cysteine, and eltrombopag have also been investigated as therapeutic strategies for PGF. However, predicting and preventing PGF remains challenging. Here, we propose that the seed, soil, and insect theories of aplastic anemia also apply to PGF; CD34+ cells are compared to seeds; the bone marrow microenvironment to soil; and virus infection, iron overload, and donor-specific anti-human leukocyte antigen antibodies to insects. From this perspective, we summarize the available information on the common risk factors of PGF, focusing on its potential mechanism. In addition, the safety and efficacy of new strategies for treating PGF are discussed to provide a foundation for preventing and treating this complex clinical problem.